2015
DOI: 10.1007/s10911-015-9339-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Progesterone on Stem/Progenitor Cells in the Human Breast

Abstract: The epithelium of the human breast is made up of a branching ductal-lobular system, which is lined by a single layer of luminal cells surrounded by a contractile basal cell layer. The co-ordinated development of stem/progenitor cells into these luminal and basal cells is fundamentally important for breast morphogenesis. The ovarian steroid hormone, progesterone, is critical in driving proliferation and normal breast development, yet progesterone analogues have also been shown to be a major driver of breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
0
4
0
2
Order By: Relevance
“…For estrogens, this will only work in those cells that co-express both GHR and ER. So far, no expression of ER has been shown in mammary stem cells, but in luminal progenitor cells the highest copy numbers of ER are found relative to unsorted cells or fully differentiated cells [34], and may therefore present cells that can be sensitive to GHR inhibition by estrogens. There is an ongoing discussion on the role of estrogens in female reproductive cancers [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…For estrogens, this will only work in those cells that co-express both GHR and ER. So far, no expression of ER has been shown in mammary stem cells, but in luminal progenitor cells the highest copy numbers of ER are found relative to unsorted cells or fully differentiated cells [34], and may therefore present cells that can be sensitive to GHR inhibition by estrogens. There is an ongoing discussion on the role of estrogens in female reproductive cancers [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…Estradiol heightens the risk of breast cancer in postmenopausal women and preclinical studies have demonstrated that progestin engenders progenitor cells in both human and breast cancer cells [ 11 12 13 ]. While estrogen and progesterone levels significantly decline following menopause, HRT-induced blood estrogen levels correlate with an increased incidence of estrogen receptor-positive breast cancer, especially in women with a higher body mass index [ 13 ].…”
Section: Hormone Therapy and Breast Cancermentioning
confidence: 99%
“…В связи с этим целесообразно рассмотреть значимые звенья патогенеза РМЖ, условно разделив их на несколько этиопатогенетических групп. Очевидным значимым фактором риска развития РМЖ является женский пол [9]. Данное обстоятельство определяет начальные этапы канцерогенеза, ключевым образом зависящие от действия эстрогенов (ERs) и прогестерона (PG) [3,10].…”
Section: Introductionunclassified